Content Analysis of Policymakers Communication Narrative Addressing Coronavirus Diseases 2019 Pandemic in Indonesia - Dasman, Hardisman; Yetti, Husna; Abdiana, Abdiana; Firdawati, Firdawati (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Coronavirus diseases 2019 (COVID-19) pandemic severely affected Indonesia in health and socio-economic sectors. As a new disease and the challenge became an opportunity for policy creation of the government. AIM: The study explored how the government as a policymaker responded to the COVID-19 pandemic within the framework of the policy window, as seen in the news media. This study also looked at how the public perceived the policy creation and the implementation. METHODS: A qualitative case study was conducted to answer the research questions by reviewing three main national news media, namely, Respublika, Media Indonesia, and Kompas, on primary communication from three policies makers (president, ministry of health, and COVID-19 task force). The searching coverage was within 1 year of the pandemic, from March 2019 to February 2020. The articles were analyzed using content and contextual analysis approaches. The articles were coded thematically using open coding in the native language, supported by MS Excel and qualitative software ATLAS.ti version 8. The data discuss with the existing literature using the policy window framework. RESULTS: We found that 147 articles were eligible for the study, which the majority of them were president communication. The president communicated in all aspects COVID-19 related policy, including integrated policy, health policy, and the economic. Ministry of health mainly focused on health policy and the task force on public education. The study showed that the government has utilized a policy window for policy creation in addressing the COVID-19 pandemic. The policy addressed all related issues that were affected by the pandemic, ranging from healthcare to financing. There were weaknesses in the implementation, such as not adequately informed to the public and some inconsistency among stakeholders. CONCLUSION: Policy creation without consistent implementation led to public distrust and rejection.